2022
DOI: 10.1101/2022.03.30.486375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fear memory in humans is consolidated over time independent of sleep

Abstract: Background: Many pathological fear memories rely on processes of fear conditioning upon an aversive event. These fear memories may continue to change after acquisition, but the factors contributing to these changes are not well understood. Sleep is known to consolidate, strengthen and change newly acquired declarative and procedural memories. However, evidence on the role of time and sleep in the consolidation of fear memories is inconclusive. Here, we used highly sensitive electrophysiological measures to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…It has previously been reported that under certain conditions, aversive memories can strengthen over long retention intervals or during extinction (i.e., nonreinforced exposure to a CS) in both human and laboratory animals (Pavlov et al, 2023;Pickens et al, 2009;Poulos et al, 2016), and this learned fear "incubation" has been hypothesized to contribute to some posttraumatic stress responses (Careaga et al, 2016;Eysenck, 1968). Relatedly, "negativity bias" (in which an individual over-values negative outcomes relative to positive outcomes; Kahneman & Tversky, 1984) results from asymmetries in the activation in memory of positive and negative valence outcomes (Norris, 2021), and it has been observed that the representation of negative outcomes tend to be more stable and recede at a slower rate than positive outcomes (Norris et al, 2010).…”
mentioning
confidence: 99%
“…It has previously been reported that under certain conditions, aversive memories can strengthen over long retention intervals or during extinction (i.e., nonreinforced exposure to a CS) in both human and laboratory animals (Pavlov et al, 2023;Pickens et al, 2009;Poulos et al, 2016), and this learned fear "incubation" has been hypothesized to contribute to some posttraumatic stress responses (Careaga et al, 2016;Eysenck, 1968). Relatedly, "negativity bias" (in which an individual over-values negative outcomes relative to positive outcomes; Kahneman & Tversky, 1984) results from asymmetries in the activation in memory of positive and negative valence outcomes (Norris, 2021), and it has been observed that the representation of negative outcomes tend to be more stable and recede at a slower rate than positive outcomes (Norris et al, 2010).…”
mentioning
confidence: 99%